Alexander Vovin, José Andrés Alonso de la Fuente, and Juha Janhunen (eds.) 2024. The Tungusic languages. Routledge Language Series. London and New York: Routledge. Pp. xxviii + 543 - Majewicz, Alfred F. (Lingua Posnaniensis, 2024)
Review